Antarctic density stratification and the strength of the circumpolar current during the Last Glacial Maximum. (12th May 2016) - Lynch‐Stieglitz, Jean; Ito, Takamitsu; Michel, Elisabeth
Abstract: The interaction between ocean circulation and biological processes in the Southern Ocean is thought to be a major control on atmospheric carbon dioxide content over glacial cycles. A better understanding of stratification and circulation in the Southern Ocean during the Last Glacial Maximum (LGM) provides information that will help us to assess these scenarios. First, we evaluate the link between Southern Ocean stratification and circulation states in a suite of climate model simulations. While simulated Antarctic Circumpolar Current (ACC) transport varies widely (80–350 Sverdrup (Sv)), it co‐varies with horizontal and vertical stratification and the formation of the southern deep water. We then test the LGM simulations against available data from paleoceanographic proxies, which can be used to assess the density stratification and ACC transport south of Australia. The paleoceanographic data suggest a moderate increase in the Southern Ocean stratification and the ACC strength during the LGM. Even with the relatively large uncertainty in the proxy‐based estimates, extreme scenarios exhibited by some climate models with ACC transports of greater than 250 Sv and highly saline Antarctic Bottom Water are highly unlikely. Key Points: ACC transport co‐varies with vertical and horizontal density stratification in models LGM data suggest modest increase in Southern Ocean density stratification and ACC transport